The new Neapolitan cinema - Marlow-Mann, Alex (Traditions in world cinema., 2011)
Vito and the Others (1991), Death of a Neapolitan Mathematician (1992) and Libera (1993), the debuts of three young Neapolitan filmmakers, stood out dramatically from the landscape of Italian cinema in the early 1990s. On the back of their critical success, over the next decade and a half, Naples became a thriving centre for film production. In this first study in English of one of the most vital and stimulating currents in contemporary European Cinema, Alex Marlow-Mann provides a detailed, multi-faceted and provocative study of this distinct regional tradition. In tracing the movement's relationship with the popular musical melodramas previously produced in Naples, he reveals how contemporary Neapolitan filmmakers have interrogated, subverted and reconfigured cinematic convention as part of a through-going re-examination of Neapolitan identity. Key features include: analyses of over 45 contemporary Italian films, including Paolo Sorrentino's The Consequences of Love, Mario Martone's L'amore molesto, Antonio Capuano's Pianese Nunzio: 14 in May and Vincenzo Marra's Sailing Home a theoretical discussion of the concept of regional cinema an examination of the movement in its broader context as both product and critique of Mayor Bassolino's 'Neapolitan Renaissance' a study of one European film industry in terms of legislation, production, distribution and exhibition. Alex Marlow-Mann has taught Italian cinema at the universities of Reading, Cardiff and Leeds and has published numerous articles on the subject. He first became interested in Neapolitan cinema when living in the city.